GIS Mapping of the Buddhist Relics of Hazara Division, Pakistan - Shakirullah; Zahoor, Muhammad (Ancient Pakistan, 2024)
The cultural activities of the Hazara region can be traced back to the early Stone Age in Pakistan, although systematic and planned archaeological investigations throughout the region in the pre- and postindependence period were scantily available. During the colonial period, there were certain efforts, largely targeted at removing treasures from Buddhist monuments and other archaeological sites. For paying attention to the culturally rich and fertile land of the Hazara Division, the Hazara University (Mansehra) got the credit to establish the Department of Cultural Heritage and Tourism Management in 2006, which later (in 2008) grew into the School of Cultural Heritage and Creative Technologies comprising of five teaching departments (i.e., Archaeology, Architecture, Art & Design, Tourism & Hospitality, and Conservation. The Department of Archaeology made serious efforts to map up the cultural relics of the Hazara region with the help of many national and international funding agencies. The current research focusses on the GIS mapping of the rich Buddhist heritage of the present eight districts of Hazara division namely, Haripur, Abbottabad, Mansehra, Batagram, Torghar, Kohistan Lower, Kohistan Upper, and Kolai Palas. The GIS technology allows for the spatial analysis of Buddhist relics’ distribution. This analysis revealed patterns of religious activities, trade routes, and cultural diffusion. By overlaying GIS data with historical records, researchers can develop new theories and insights into the dynamics of ancient civilizations in the region. GIS mapping of these relics will help develop the tourism industry by making it easier for travellers and tourists to locate and study these assets of archaeological and historical interest.